Dampak Perpres No. 126 Tahun 2022 Terhadap Upaya Mencapai Swasembada Garam 2024 - Firdha Usmina Safitri; Atika Puspita Marzaman (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Indonesia, as the world's largest archipelagic state, possesses vast maritime territories, including 3.2 million km2 of territorial waters and a 2.7 million km2 Exclusive Economic Zone (EEZ). The maritime expanse provides diverse marine resources, notably significant salt production potential. Despite its extensive coastline and marine environment, Indonesia's national salt production in 2021 and 2022 fell significantly short of the 4.5 million-ton domestic demand, highlighting a substantial gap in achieving self-sufficiency. This reliance on salt imports poses economic and food security vulnerabilities, prompting the government to enact Presidential Regulation No. 126/2022, aiming to accelerate national salt development.